Investigation on key factors promoting internal control implementation effectiveness in higher education institution: The case of Indonesia - Hafiez Sofyani; Zakiah Saleh; Haslida Abu Hasan (Universitas Muhammadiyah Malang, 2021)
This study aims to investigate the key factors promoting internal control implementation effectiveness in Indonesian Higher Education Institutions (HEIs). This study uses a qualitative approach by employing interviews as data collection technique. 13 informants were involved, consisting of management members of internal control unit, top management of HEI, and HEI accreditation assessor. The results reveal that to achieve effective implementation of internal control, seven key factors must be considered, including: (1) Management and foundation roles; (2) Awareness of all organization members; (3) Sufficient and competence of human resources; (4) Internal auditor attitude; (5) Organizational climate; (6) IT support; and (7) Funding support. The results of this study address research gaps related to internal control studies in the context of HEI, especially in developing countries, which according to Chalmers et al. (2019) still gets very little attention by accounting scholars.